2015
DOI: 10.1002/art.39281
|View full text |Cite
|
Sign up to set email alerts
|

Performance on the Adult Rheumatology In‐Training Examination and Relationship to Outcomes on the Rheumatology Certification Examination

Abstract: Objective. The American College of Rheumatology (ACR) Adult Rheumatology In-Training Examination (ITE) is a feedback tool designed to identify strengths and weaknesses in the content knowledge of individual fellows-in-training and the training program curricula. We determined whether scores on the ACR ITE, as well as scores on other major standardized medical examinations and competency-based ratings, could be used to predict performance on the American Board of Internal Medicine (ABIM) Rheumatology Certificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 12 publications
3
14
0
Order By: Relevance
“…Like other recent studies [8,9], we found performance on the ITEs designed for hematology and oncology trainees to be predictive of performance on subsequent ABIM IM subspecialty certification examinations. This was especially important when the results in the final year of training were considered.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Like other recent studies [8,9], we found performance on the ITEs designed for hematology and oncology trainees to be predictive of performance on subsequent ABIM IM subspecialty certification examinations. This was especially important when the results in the final year of training were considered.…”
Section: Discussionsupporting
confidence: 82%
“…The first administration of these examinations was in 2009 and 2008, respectively. ITE scores have been associated with subsequent specialty board certification in IM and board certification in the subspecialties of infectious disease and rheumatology [5][6][7][8][9]. The NBME's United States Medical Licensing Examination (USMLE), a three-step examination taken in medical school, also positively predicts performance on the IM certification examination [10].…”
Section: Introductionmentioning
confidence: 99%
“…While there are limited studies on the predictive role of in-training assessment in GP training, numerous studies in other specialities have identified the predictive role of in-training examinations in fellowship exams. [29][30][31] The internal MCQs were designed as formative feedback tools to assist the trainees and trainers to assess mastery of content and competence while serving as a guidepost for the fellowship examination. 32 Evidence from our study has enabled the JCU GPT programme to intervene early in providing additional support for trainees at risk of failing to progress through the training programme.…”
Section: Discussionmentioning
confidence: 99%
“…In-training examinations can provide objective evidence regarding a trainee's readiness to successfully complete the corresponding board certification examination and thus, allow implementation of remediation plans if needed. A growing number of studies have indicated that in-training examination performance has a positive relationship with performance on the respective board certification examination within a variety of medical specialties (3)(4)(5)(6)(7)(8)(9)(10). Generally, average to high scores on these examinations yield a high probability of passing the respective board certification examination.…”
Section: Introductionmentioning
confidence: 99%